The Influence of Central Government Transfers and Local Own-Source Revenue on Capital Expenditure in Regional Governments - Syaifullah, Akhmad; Romli, Romli (Dinasti Publisher, 2025)
This study aims to examine the effect of central government transfers and local own-source revenue on capital expenditure in 27 regencies and municipalities in West Java Province over the 2019–2023 period. The research employed a quantitative approach using multiple linear regression analysis, supported by statistical testing through t-test and F-test. The study used secondary data obtained from regional budget realization reports and the official website of the Directorate General of Regional Fiscal Balance, Ministry of Finance of the Republic of Indonesia. The findings indicate that both central government transfers and local own-source revenue have a positive and significant effect on capital expenditure. The adjusted R-squared value of 0.742 reveals that 74.2% of the variation in capital expenditure is explained by the two independent variables. These results suggest that increased local revenue enhances fiscal capacity, enabling local governments to finance long-term development projects without relying entirely on central transfers. Furthermore, the higher coefficient of local revenue compared to that of central transfers indicates that the flypaper effect did not occur during the study period. Overall, the findings affirm that the implementation of fiscal decentralization has begun to strengthen the fiscal independence of subnational governments, particularly in making more autonomous and productive capital expenditure decisions.